Compound salvia pellet might be more effective and safer for chronic stable angina pectoris compared with nitrates: A systematic review and meta-analysis of randomized controlled trials. Issue 9 (March 2019) - Huiping, Wei; Yu, Wang; Pei, Jin; Jiao, Li; Shian, Zhang; Hugang, Jiang; Zheng, Wang; Yingdong, Li
Abstract: Background: Chronic stable angina (CSA) resulted in a considerable burden for both individuals and the society. In this study we aimed to critically evaluate the effectiveness and safety of Compound salvia pellet compared with nitrates in the treatment of Chronic Stable Angina (CSA) pectoris, and to provide more credible evidence for clinical practice. Methods: A comprehensive and exhaustive search strategy was formulated to identify potential RCTs of compound salvia pellet for CSA in international and Chinese databases from their inception to July 4th, 2018. We also searched the bibliographies of relevant studies. Two reviewers independently assessed the quality of included trials by using Cochrane Risk of Bias Tool. Results: The literature search yielded 1849 citations and 51 RCTs (n = 4732) were included for meta-analysis after titles, abstracts and full text selection according to eligibility criteria. The pooled results suggested that compound salvia pellet was much more effective than nitrates in the improvement of angina symptoms (therapy = 4 weeks, RR = 1.23, 95%CI = [1.17, 1.30], P  < .001, I 2  = 0%; therapy = 4 weeks, RR = 1.13, 95%CI = [1.08, 1.17], P  < .001, I 2  = 45.6%), and ECG test (therapy = 4 weeks, RR = 1.24, 95%CI [1.14, 1.35], P  < .001, I 2  = 51.5%; and therapy > 4 weeks, RR = 1.30, 95%CI[1.20, 1.42], P  < .001, I 2  = 36.4%) in CSA. Compared with nitrates, the percentage of patients with adverse events significantly decreased when prescribed with compound salvia pellet (3.2% vs 17.0%). Conclusion: Compound salvia pellet might be more effective on the improvement of angina symptoms, ECG test and with few adverse events compared with nitrates. While there are some limitations in this study, which may weaken the results, we believe the findings could provide useful information for stakeholders concerned with outcomes in patients with CSA. More rigorous RCTs with high quality are needed to confirm these findings. Abstract : Supplemental Digital Content is available in the text